New integrative methodology for the excavation and study of mass graves and partially commingled remains - Marcos De Andrés Montero; Luca Kis; Olga Spekker; Viktor Vig; Réka Kocsmár; Zsófia Simon; Béla Simon; Réka Neményi; Gábor Bertók; Balázs Tihanyi; György Pálfi (PLoS ONE, 2026)
The resolution of commingled human skeletal remains is a phenomenon increasingly encountered by archaeologists and anthropologists. Its difficulty is due to the complexity of the task itself, but also to the limited methodological resources available for researchers. Parallelly, its importance derives from the fact that individualized skeletons are a prerequisite for any anthropological analysis that aims to provide results. In this paper, we put forward a new methodological approach that aims to integrate different tools and techniques already available. The basis of this methodology is the analysis of the spatial relationships of the human skeletal remains. To facilitate its use and maximize its effectiveness, we have developed a set of specific tools and protocols that include a list of information to be directly recorded in Geographical Information System (GIS) software, as well as a new coding system for skeletal remains showing different levels of completeness. Results show that the application of such a methodology helped in the resolution of a large, commingled assemblage exhumed from a 16 th -century-CE burial located in southwestern Hungary. The original number of complete skeletons (those individualized in their entirety during the fieldwork) was substantially increased, and for several other skeletal elements, potential matches were found during the laboratory work. We found this methodology to be a good filter prior to the utilization of the more standardized techniques such as osteometric sorting, articulation, visual pair-matching or process of elimination, as it would increase their effectiveness. Additionally, the novel coding system has proven to be useful in inventorying and storing human skeletal remains. This project shows that the addition of GIS technology and spatial analysis does increase the success rate in the reassociation of commingled human skeletal remains.